Possible origins of different usages in Present-Day spoken and written English - Wolf, Gőran (Adam Mickiewicz University, 2007)
Within the continuum of spoken and written English some variations, e. g. the varying usage of negation and the opposition of pronominal usage, can be explained with reference to the varying characteristics of speech and writing. The origins of these variations, however, cannot be explained along these lines. After rendering some basic concepts, I would like to propose a view which accounts for the given variations with regards to the mentioned period of the history of the Standard English dialect. The paper will show that quite a lot of the variations which nowadays occur along the spoken/written divide equal those features which early grammarians, such as Robert Lowth or Joseph Priestley, discussed referring to good or bad language use. Therefore, I would like to argue that the grammatical structures found in spoken or written Present Day English originate from suggestions for seventeenth- and eighteenth-century norms of English.